2006
DOI: 10.1073/pnas.0604430103
|View full text |Cite
|
Sign up to set email alerts
|

The significance of direct sunlight and polarized skylight in the ant’s celestial system of navigation

Abstract: As textbook knowledge has it, bees and ants use polarized skylight as a backup cue whenever the main compass cue, the sun, is obscured by clouds. Here we show, by employing a unique experimental paradigm, that the celestial compass system of desert ants, Cataglyphis, relies predominantly on polarized skylight. If ants experience only parts of the polarization pattern during training but the full pattern in a subsequent test situation, they systematically deviate from their true homeward courses, with the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
174
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(177 citation statements)
references
References 18 publications
2
174
0
1
Order By: Relevance
“…The difference between Myrmecia and other ants may reflect differences in the visual ecology of different species, in particular in the context of navigation. For instance, Cataglyphis ants rely predominantly on path integration and, as part of this, on the pattern of polarized skylight as a compass reference [21], for which colour vision would not seem to be required. Ants in landmark-rich habitats however, including the two species studied here, are guided by the visual panorama, often in preference to path integration information (e.g.…”
Section: (B) Are Australian Ants Special?mentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between Myrmecia and other ants may reflect differences in the visual ecology of different species, in particular in the context of navigation. For instance, Cataglyphis ants rely predominantly on path integration and, as part of this, on the pattern of polarized skylight as a compass reference [21], for which colour vision would not seem to be required. Ants in landmark-rich habitats however, including the two species studied here, are guided by the visual panorama, often in preference to path integration information (e.g.…”
Section: (B) Are Australian Ants Special?mentioning
confidence: 99%
“…Ants such as C. bicolor and Cataglyphis fortis, which live in landmark-poor deserts and salt pans, for instance, use the pattern of polarized skylight as a compass reference for their path integration system [18,21,26,27]. Ants such as the Australian desert ant Melophorus bagoti that inhabit landmark-rich environments containing grass tussocks, shrubs and trees, rely more heavily on information provided by the visual landmark panorama to find home [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in clear skies. It was shown that in the field, desert ants choose the sky polarization pattern or even part of it as a primary compass for navigation even when the Sun disc is visible [2]. Other insects, such as spiders [3] and field crickets [4], have also been shown to use sky polarization for navigation.…”
Section: Introduction (A)mentioning
confidence: 99%
“…It is unlikely that squid perform such calculations in each case, but it can be expected that a distance estimation system is hard-wired in their nervous system or acquired over time and experience. Such a neurological approach for polarization calculations can be found in compact nervous systems such as those of insects [39,40].…”
Section: Polarization and Detection Of Bioluminescent Sourcesmentioning
confidence: 99%